2009
DOI: 10.1080/15367100802665540
|View full text |Cite
|
Sign up to set email alerts
|

Social-Psychological Support Personnel: Attitudes and Perceptions of Teamwork Supporting Children With Disabilities

Abstract: This article used a mixed methods design to analyze attitudes and perceptions of social-psychological support personnel serving on school-based teams supporting children with disabilities. Results suggest that the 76 respondents held a generally positive attitude about teamwork. Qualitative analyses of open-ended responses found discipline collaboration and sharing information and perspectives as benefits of the team process. Perceived limitations of the team process included time constraints and a lack of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
3
0
2
Order By: Relevance
“…Additional help in the form of social support is necessary for parents raising children with DDs (Gallagher et al 2009 ; McConnell et al 2014 ). However, 74 % of parents of the 3.7 % of children with disabilities living in Canada reported that extra help was too expensive for them, and many stated difficulty in finding and accessing appropriate resources (Statistics Canada 2006 ).…”
mentioning
confidence: 99%
“…Additional help in the form of social support is necessary for parents raising children with DDs (Gallagher et al 2009 ; McConnell et al 2014 ). However, 74 % of parents of the 3.7 % of children with disabilities living in Canada reported that extra help was too expensive for them, and many stated difficulty in finding and accessing appropriate resources (Statistics Canada 2006 ).…”
mentioning
confidence: 99%
“…Furthermore, the presence of other professionals in the school environment, such as social workers, helps to improve the educational experience of students (Gallagher, Malone, & Ladner, 2009). For example, in inclusive education settings, social workers can function as liaisons between the school, the home, and the community and connect all relevant stakeholders to resolve problems that students may be facing in school (Mittler, Jackson, & Sebba, 2002).…”
Section: Social Workers In Inclusive Educationmentioning
confidence: 99%
“…Stress in the workplace is a concern among various caring professionals (Breen, Wildy and Saggers, 2011;Gallagher, Malone and Ladner, 2009;Shyman, 2010). Religion offers help for many in understanding and coming to terms with stressful life events.…”
Section: Stress Religious Coping and Meaning-makingmentioning
confidence: 99%